Pengaruh Alokasi Dana Desa terhadap Pertumbuhan Ekonomi: Studi Empiris pada Daerah Tertinggal di Indonesia pada Tahun 2019-2020 - Muhammad Fadhil Zain; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to provide empirical evidence regarding the influence of village fund allocation on economic growth in underdeveloped regions in Indonesia in 2019-2020. This research uses quantitative descriptive methods and is grouped into causative research. The population in this research is the allocation of village funds to disadvantaged areas in accordance with Presidential Decree Number 63 of 2020 concerning the Determination of Disadvantaged Regions for 2020-2024, which consists of 62 districts. The sampling technique in this study used a saturated sample technique, where the number of samples in this study was 62 samples with a total sample size of 124 samples. The type of data used is secondary data obtained from the recapitulation of the 2019-2020 BPS Indonesia survey report. The data analysis method uses simple linear regression analysis. The results of this research show that village fund allocation has a positive and significant influence on the economic growth of underdeveloped regions in Indonesia in 2019-2020.